Frequencies, clinicopathological features, and risk factors of type I and type II endometrial cancer; a retrospective observational study at a tertiary care hospital in Pakistan - Nawaz, Muhammad Talha; Hameed , Ayesha Nasir; Tauqeer , Hassan; Angez, Meher; Aziz, Aliya Begum (International Journal Of Community Medicine And Public Health, 2023)
Background: Endometrial cancer (EC) is the most common gynecological malignancy worldwide. The death rates for EC have increased by more than 100% over the past 2 decades. EC is subdivided into two types based on distinct histological and clinical features: type I and type II. Our study aims to determine the risk factors and clinicopathological features of both type I and type II EC and draw a comparison between the two types based on frequency, risk factors and clinicopathological features. Methods: It was a retrospective observational study including patients of a single tertiary care center. The study included Patients diagnosed, treated, and followed up for type I and type II endometrial cancer at the study center over the past 19 years from 1st January 2000 to 31st December 2018. All the patients with metastatic endometrial cancer were excluded from the study. SPSS version 26 was used for statistical analysis. Results: A total of 376 patients were included in this study. Among these 343 (91.7) patients had endometroid adenocarcinoma (Type I) and 32 (8.3) had serous and clear cell tumor (type II). Type I EC had a mean age of 57.56 (SD±10.42) while patients with type II EC presented with a mean age of64.97 (SD±6.59). Hypertension and Diabetes were the most common comorbid in EC patients. HRT prior to EC was found to have an association with risk of EC. Compared to patients who were on HRT, patients who were not on HRT prior to diagnosis of EC had 80% less chance of developing endometrial cancer. (Confidence interval: 0.056-0.114, p=0.016). Conclusions: In summary our study demonstrates that both sub types of endometrial cancer have many risk factors that are similar to each other. Despite the difference between the population of both subgroups we were able to prove associations between risk factors and endometrial cancer. However further research is needed at provincial and national level with larger and relatively comparable sample sizes for both subgroups to recognize risk factors and numerically associate them to EC for Pakistani population.